EARLY CHILDHOOD SOCIAL AND EMOTIONAL DEVELOPMENT IN ISLAMIC EDUCATION - Hikmah, Nurul (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Social and emotional development is an individual's ability to adapt to their environment by the rules of Allah and the Messenger. Meanwhile, early childhood education in Islam is a conscious effort to prepare children to enter the tamyiz phase (the phase where children know good and evil according to Allah and the Messenger according to their age). This research aims to discuss early childhood social and emotional development in Islam, considering that the social and emotional development of children in Islam has characteristics. This research uses a qualitative methodology, where the data sources are primary data and secondary data. The results of this research explain that the social and emotional development of early childhood in Islam has two dimensions: divine and human.